Systematic Literature Review: Key Determinants for Quality Destination Development in Sustainable Urban Tourism (Case Study: Jakarta) - Hubner, Ira B.; Rahmanita, Myrza (International Journal of Economics Development Research (IJEDR), 2024)
Global tourism has shown a remarkable recovery in 2024, with Indonesia ranking 22nd in the Travel and Tourism Development Index. Indonesia has made significant advancements in sustainable tourism, particularly by focusing on socio-economic, environmental, and demand sustainability. However, challenges persist, including low-quality services and over-tourism in urban areas, which impact local resources and communities. To address these issues, the Indonesian government introduced quality tourism initiatives at the International Quality Tourism Conference 2024. These initiatives aim to balance supply-side improvements in competitiveness, infrastructure, and sustainable management with demand-side enhancements that emphasize unique and high-value experiences for tourists. This approach aligns with Indonesia’s National Medium-Term Development Plan (2024-2029), which seeks to prioritize quality over quantity, thus ensuring sustainable tourism growth and enhancing local cultural and environmental preservation. Urban tourism, particularly in Jakarta, has been identified as a key area for quality tourism enhancement. Although Jakarta welcomed nearly two million international tourists in 2023, it still lags in global urban tourism rankings, highlighting the need to strengthen its destination competitiveness. This study, using systematic literature review methods, explores the current status of urban tourism research, focusing on destination quality and competitiveness. Bibliometric analyses, conducted through VOSviewer software, reveal thematic clusters in urban tourism, such as sustainability, smart tourism, and over-tourism, underscoring the increasing importance of quality management and competitive strategies in urban tourism. Findings suggest that The determining factors toward the quality destination of urban tourism are: sustainability, competitiveness, quality of life (impact of tourism), smart city and smart tourism.